Dermatomyositis Presented with Facial Rash in a 40 Years Old Lady in Bangladesh: A Case Report - Sabeka, Meera Momtaz; Hussain, Mohammad Enayet (Journal of National Institute of Neurosciences Bangladesh, 2019)
Dermatomyositis is overly simplified as inflammatory myopathy with characteristic rashes. Understanding dermatomyositis is challenging because firstly presentation may be non-specific, vague and delayed. Secondly there is no specific diagnostic test or universally acceptable diagnostic criteria. Therefore, to missed or delayed diagnosis results in failure to treatment. A forty year old lady with facial rash and generalized weakness was diagnosed with dermatomyositis on the basis of generalized weakness, typical facial rash with very high CK and eletrophysiological study. Steroid treatment initially improved her symptoms. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 191-193